CONSUMER SOCIALISATION OF OVER-THECOUNTER MEDICINES: DOES CULTURE MATTER? - Abdul Hamid, Suriani; David, Cohen; Valarie, Manna (Management Research Journal, 2019)
Self- medication with over-the-counter medicines (OTCs) is common practice not only for adults, but also among adolescents. Tapping into this potentially lucrative segment of adolescents as consumers will require marketers and academic researchers to understand this market well. The long-term benefits are worthy of focus as the buying patterns developed during teenage years are likely to continue throughout adult lives. Furthermore, as this population begins to age, they become a stronger customer base for pharmaceutical products. The majority of studies about OTCs have been conducted from the perspective of pharmacists or healthcare professionals in medical sociology, pharmacy practice and public policy. Very limited research has examined these products from the consumer behaviour perspectives.Using a consumer socialisation perspective, this study seeks to understand how adolescents learn to use OTCs. The study aimed to understand similarities and differences between adolescents living in Malaysia and New Zealand with respect to this product class. Data was collected at high schools in Christchurch, New Zealand and Johor Bahru, Malaysia. A total of 509 (New Zealand n=276 and Malaysia n=233) usable responses were obtained. Overall, the results of this study showed that self-medication with OTCs was widespread among respondents with a high percentage of them having purchased the medicines themselves. The results of this study also suggested that there were some differences and similarities among adolescents in New Zealand and Malaysia when it came to OTC-related consumer socialisation.